THE INFLUENCE OF WORK ENVIRONMENT AND SALARY ON EMPLOYEES' JOB SATISFACTION AT AROFAH ISLAMIC HOSPITAL IN MOJOSARI, MOJOKERTO - Darmawan, Muhammad Syahrul Rizal; Santoso, Bowo (Yayasan Education and Social Center, 2024)
This research aims to determine and analyze the influence of the work environment and salary on employee job satisfaction at the Arofah Islamic Hospital in Mojosari, Mojokerto. Using a quantitative approach with a causal research design, this research involved 43 employees as the population and sample. The data used consists of primary and secondary data. The data analysis technique applied is Partial Least Square (PLS). The research results show that both the work environment and salary have a positive and significant influence on employee job satisfaction at Arofah Islamic Hospital. These findings emphasize the importance of work environment factors and compensation in increasing employee job satisfaction in the health sector. Thus, hospital management is advised to continue to improve working environment conditions and salary structures in order to increase employee satisfaction and productivity. This research provides important insights for human resource management in health institutions